2008
DOI: 10.1037/0893-164x.22.3.426
|View full text |Cite
|
Sign up to set email alerts
|

Working memory capacity moderates the predictive effects of drug-related associations on substance use.

Abstract: Some theories suggest that spontaneously activated, drug-related associations in memory may have a “freer reign” in predicting drug use among individuals with lower working memory capacity. This study evaluated this hypothesis among 145 at-risk youth attending continuation high schools (CHS). This is the first study to evaluate this type of dual-process interaction in the prediction of drug use among a sample of at-risk adolescents. The CHS students completed assessments of drug-related memory associations, wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
168
5
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 214 publications
(193 citation statements)
references
References 54 publications
13
168
5
7
Order By: Relevance
“…Studies have also shown that when executive functions are weak, impulsive processes predict behaviour. When executive functions were strong, reflective processes predict behaviour (e.g., Thush et al 2008;Grenard et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that when executive functions are weak, impulsive processes predict behaviour. When executive functions were strong, reflective processes predict behaviour (e.g., Thush et al 2008;Grenard et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of implicit-and explicit attitudes and their underlying processes has recently attracted attention (see also Grenard et al 2008;Thush et al 2008) in the prediction of a variety of behaviors including aggression (Schröder-Abé et al 2007a, b). For example, in a study on interracial interactions it was found that for low levels of inhibition, implicit racial attitudes predicted interracial interactions and for high levels of inhibition, explicit racial attitudes predicted these interactions (e.g., the competitiveness of the confederate reported by the participants, and the talkativeness of the participant; Hofmann et al 2008).…”
mentioning
confidence: 99%
“…Further, individuals with high social deviation and low short-term memory capacity than the individuals with high social deviation and high short-term memory capacity have reported higher scores in Michigan Alcoholism Screening Test (MAST). Grenard et al (2008) in their study reported that associations related to drug among adolescents exposed to low working memory capacity compared to individuals with high working memory capacity are stronger forecasts for alcohol and cigarette abuse. Ellingson et al (2004) obtained the same results with the findings of research by Finn & Hall (2004).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this group is more likely subjected to risk. Grenard, Ames, Wiers, Thush, Sussman& Stacy (2008) in another study concluded that associations to drugs in memory forecast drug use in a stronger way in students with lower levels of working memory capacity. Hofmann, Gschwendner, Friese, Wiers & Schmitt (2008) in their study found that impulsive processes determining behavior are more prevailed in the individuals who lack the required working memory capacity.…”
mentioning
confidence: 99%